Logiques de projet et régulation publique de l’information géographique - Louca Lerch (Netcom)
Based on the experience of the spatial data infrastructure project carried out by the Bolivian Government (GeoBolivia), this article aims at studying the geo-environmental information data heritage owned by the country after two decades of « by project » and « remote » public action. The « projectorate », which has been a characteristic feature of Bolivia until the first decade of the 21st century as well as of other countries of the “globalized South”, corresponds to the proliferation of uncoordinated development projects financed by foreign international actors. I propose to extend the concept of « projectorate » to the process of production of segmented geographical information that cannot be re-appropriated beyond the logic of projects. The GeoBolivia initiative aims at overcoming this situation by capitalizing existing information and producing a national data infrastructure which would allow a « social control » of the existing geographical information as well as an overview of the gaps to be filled regarding the production of geographical knowledge. The capacity of the GeoBolivia initiative to contribute to a « post-neoliberal » regulation and redistribution of geographical information, as well as the contradictions of such an initiative, will be analyzed in the light of Foucault’s concept of govermentality.